Pengembangan Maqasid Al-Syari’ah Perspektif Thahir Ibnu ‘Asyur - Sholikah, S (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
The essence of Islamic law is to attract the good (maslahat) of humans and reject the danger from it. Therefore, in addition to carrying out the shari'ah, humans are required to understand the aims and objectives of the shari'ah set. Departing from the above statement, this study will examine the efforts of Thahir ibnu ‘Asyur in developing concepts related to the science of maqasid al-shari'ah.The data of this research is library. The data collection method uses the documentation method, which is: collecting, then analyzing the data collected. After the data has been collected, data analysis is carried out by means of data reduction, presentation of data in narrative form, and drawing conclusions.This study concludes that the maqasid al-shari'ah, as stated by Thahir ibnu ‘Asyur, is the spirit of all human actions relating to the laws established by Islamic shari’ah, especially in dealing with a number of problems in this millennial era. In addition, said Thahir ibnu ‘Asyur, the main reason for the decline of fiqh is the neglect of scholars towards the study of maqasid which results in the distortion of shari'ah values themselves. The opinion of Thahir ibnu ‘Asyur above is supported by ‘Allal al-Fasi, one of the experts in contemporary maqasid al-shari’ah, who asserted that the main condition for success in dialoguing fiqh with contemporary reality is the rise or failure of scholars' responses to the study of maqasid. This is where the role of maqasid al-shari'ah as the spirit of each fiqh law finds its momentum. Its elastic characteristics, across space and time, are expected to be able to dialogue with problems that continue to emerge. These characteristics are able to adapt to every civilization that runs and play a role in arousing Islamic civilization that is lagging behind other civilizations.